Advance Care Planning in a Geriatric Primary Care Clinic: A Retrospective Chart Review. (January 2019) - Barkley, Ariana; Liquori, Mike; Cunningham, Amy; Liantonio, John; Worster, Brooke; Parks, Susan
Purpose: Advance care planning (ACP) is theorized to benefit both the patient and their family when end of life is near as well as earlier in the course of serious illness. However, ACP remains underutilized, and little is known about the nature of ACP documentation in geriatrics practices. The study investigated the prevalence and nature of ACP documentation within a geriatric primary care clinic. Methods: A retrospective chart review was conducted on a randomly selected sample of electronic medical record (EMR) charts. The sample consisted of patients aged 65 and older who were seen in the clinic from January 1, 2015, to December 31, 2016. Charts were reviewed for ACP documentation and data regarding age, gender, race, religion, comorbidities (end-stage renal disease, congestive heart failure, cancer, and dementia), recent hospitalizations, and visit type. Results: Ninety-eight charts were reviewed (n = 98). Nine patients (9.18%) had an advance directive (AD) or power of attorney (POA) available within their EMR. Twenty-five patients (25.5%) had provider notes documenting that they have an AD, POA, or preferred health-care decision maker; however, no documents were available. The remaining 64 (65.3%) patients had no evidence of ACP documentation within their EMR. Age was the only demographic variable associated with completion of an AD ( P = .038). Discussion: The rate of ACP documentation (34.6%) was lower than the average among US adults aged 65 and over (45.6%); further, most patients with ACP documentation did not have an AD or POA on file. The authors plan to reevaluate ACP statistics in the same office following a future intervention.